More than just a formative assessment: Assessment for learning as a driver for critical thinking, democracy and positive classroom relationships - Batey, Edward (2015)
Assessment for learning (Afl) has become an integral part of current educational philosophy - both teachers and schools are judged on their ability to implement it effectively. Nearly two decades since Afl's appearance, opinions differ on exactly what it constitutes. General co nsensus agrees that Afl has as its base a strong commitment to high quality formative assessment, but influential academics argue that Afl has deeper implications involving student voice and student ownership of their learning.